النخور السنية والحاجة للمعالجة التقويمية عند أطفال بعمر 12-10 سنة من مدينة دمشق. - نوايا, فهمية; برهان, أحمد (Latakia University Journal -Medical Sciences Series, 2016)
الخلفية والهدف:تعد النخور السنية وسوء الإطباق من أكثر الأمراض السنية المزمنة شيوعاً في مرحلة الطفولة. إن الهدف من الدراسة الحالية هو تقييم شدة النخر السني والحاجة للمعالجة التقويمية والعلاقة بينهما عند عينة من أطفال مدارس مدينة دمشق بعمر 12-10 سنة.مواد وطرائق البحث: شملت هذه الدراسة المقطعية 1428 طفلاً (677 ذكراً و 751 أنثى) كانوا جميعهم في مرحلة الإطباق المختلط المتأخر، ولم يسبق لهم أن تلقوا أي معالجة تقويمية. تم تقييم الصحة السنية لديهم باستخدام مشعر DMFT، كما تم تقييم حاجتهم للمعالجة التقويميـة باستخدام عناصر الصحة السـنية لمشـعر الحاجة للمعالجة التقويمية DHC-IOTN. تمت المقارنات الإحصائية باستخدام اختبارات 2-sample t-test، Chi-square،One-way ANOVA ، Bonferroni. وتم الحكم على النتائج عند مستوى الثقة 95%. النتائج:بلغ متوسط مشعر النخر السني DMFT في العينة الكلية4.4 ±3.2، وبدون فروق جوهرية بين الذكور والإناث (P=0.705). كان هناك حاجة شديدة أو ملحة للمعالجة التقويمية (الدرجتين الرابعة والخامسة من مشعر DHC-IOTN) عند 341 طفلاً، بنسبة 23.88% من أفراد العينة، وبدون فروق جوهرية بين الذكور والإناث (P=0.71). كانت شدة النخور السنية أعلى بشكل جوهري عند المرضى الذين لديهم الدرجات الأشد من الحاجة للمعالجة التقويمية.الاستنتاجات:إن مشعرDHC-IOTN هو مشعر موثوق سهل الاستخدام، ينصح باستخدامه في دراسات تقويم الأسنان الوبائية. تترافق الحالات الأشد من الحاجة للمعالجة التقويمية مع معدلات أكبر للنخور السنية، لذا ينصح بالمعالجة المبكرة لكل منهما بالإضافة إلى اتخاذ كافة الإجراءات الوقائية على المستوى الوطني.Background and Aim: Dental caries and malocclusion are among the most common chronic dental diseases in childhood. The aim of present study was to assess the severity of dental caries and orthodontic treatment needs and the relation between them in a sample of 10- to 12-year-old Damascus schoolchildren.Methods: This cross-sectional study included 1428 children (677 males and 751 females), all were in the late mixed dentitions and orthodontically untreated. Their dental health status was assessed using DMFT index and need for orthodontic treatment by the dental health component of the index of orthodontic treatment need (DHC-IOTN). Analytical statistics were calculated using 2-sample t-test, Chi-square, One-way ANOVA and Bonferroni tests. All the results were judged at a 95% confidence level.Results: The overall mean of DMFT was 4.4±3.2 without significant differences between males and females (p=0.705). Extreme and severe need for orthodontic treatment (grades 4 and 5 of IOTN) was registered in 341 subjects (23.88%), without significant differences between males and females (p=0.710). The severity of dental caries was significantly greater among patients with more severe grades of orthodontic treatment need.Conclusions: The DHC-IOTN index is reliable and userfriendly, which can be used for orthodontic epidemiological studies. There is significant relation between higher DMFT index and orthodontic treatment need. Therefore, early treatment and preventive national programmes is strongly advised.